A postcolonial reading of the Acts of the Apostles - Muñoz-Larrondo, Rubén (Studies in biblical literature, 2012)
Postcolonial criticism as an optic for biblical studies -- The death of Herod Agrippa I as starting point -- Roman imperial worship : presuppositions for the study -- Representation in Acts of the institutions of Judaism -- The Roman representation in the Acts of the Apostles